Assessing Toxicity of The Alcoholic Extract of "Myrtus communis L." leaves on The Human Lymphocytes - إبراهيم , نهلة (Latakia University Journal -Biological Sciences Series, 2022)
This study aimed to test the toxicity of the alcoholic extract of Myrtus communis L. leaves by studying the effect of different concentrations of the extract on cell division, programmed cell death and Cell Cycle in human lymphocytes. Human lymphocytes werecultured by whole blood culture method, and the alcoholic extract of Myrtus communis L. leaves was added to (five different concentrations 2 10, 25, 50 and 100 μg/ml), then the effect of the above-mentioned concentrations on the rate of lymphocyte division and programmed death rate and on the different stages of the Cell Cycle was studied.The results showed that the extract with its different concentrations helped in the division of lymphocytes cells, the percentage of dividing cells increased, and the concentrations of 2 and 100 μg/ml were the most inducing lymphocytes to divide.The alcoholic extract of Myrtus communis L. leaves did not affect the different phases of the Cell Cycle, so there were no significant differences between the control and the different concentrations of the extract. In addition, the extract did not cause cells to entering into programmed cell death significantly, there were no significant differences between the control and the different concentrations of the extract, and the concentrations of 25 and 50 μg/ml were the most effective in entering cells into programmed cell death. Myrtus communis L. is safe to use and non-toxic.